Pengaruh Inflasi dan BI Rate terhadap Simpanan Masyarakat pada Bank Umum Pemerintah di Indonesia Tahun 2010-2019 - Selfiana Mery Anggraini; A. A. Sri Purnami; I Gusti Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2021)
The purpose of the research is to analyze the effect of Inflation and BI Rate on Public Savings at Goverment Commercial Banks in Indonesia on 2010-2019. Partially, Inflation has a negative effect on public savings, while BI Rate has a positive effect on public savings at Government Commercial Banks in Indonesia on 2010-2019. Data analysis tools used are the classical assumption test and hypothesis testing with multiple linear regression methods. The result of the research is the Inflation and BI Rate simultaneously (together) had a positive and significant effect on public savings at Government Commercial Bank in Indonesia. While partially, Inflation has a negative and not significant effect on public savings at Government Commercial Bank in Indonesia.